Comparison of vNOTES technique with conventional laparoscopy in gynecological emergency cases - Karakaş, Sema; Kaya, Cihan; Yildiz, Şükrü; Alay, İsmail; Durmuş, Uğur; Aydiner, İlke Esin; Ekin, Murat (Minimally invasive therapy and allied technologies, 2022)
Vaginal natural orifice transluminal endoscopic surgery (vNOTES) has emerged as a minimally invasive approach. This study aimed to evaluate the feasibility and surgical outcomes of the vNOTES method and compare it with conventional laparoscopy (CL) in gynecological emergency cases. A retrospective study was conducted to compare vNOTES with CL regarding pre-/intra-/postoperative outcomes. The women who were operated on for emergency indications such as ectopic pregnancy, ovarian torsion, ovarian cyst rupture and acute abdominal pain were evaluated. Patients' age, gravidity, parity, medical/surgical history, height, weight, blood pressure, heart rate, pre-/postoperative hemoglobin and hematocrit levels, the quantity of aspirated hemoperitoneum, visual analog scale (VAS) pain scores six and 12 h postoperatively, duration of surgery and hospital stay were recorded. The study was conducted with 90 women. Sixty of them underwent CL, while 30 women had vNOTES. The vNOTES group had a significantly shorter duration of surgery −28.5 min (15-48 min) vs. 77 min (29-155 min), respectively, p < .001), shorter hospital stay − 32 h (11-125 h) vs. 38 h (12-201 h), respectively, p = .007), lower VAS scores after 6 h - 5 (4-7) vs. 6 (2-8), respectively, p < .001), and after 12 h − 2 (1-3) vs. 2 (1-5), respectively, p < .001) and a lower dose of postoperative analgesic administration − 2 (2-3) vs. 3 (1-5), respectively, p < .001) than the CL group. vNOTES surgeries can be considered an alternative technique to CL by providing shorter surgery duration, lower postoperative pain scores, shorter hospital stays and better cosmetic outcomes.